Do reduced labor costs increase employment among minimum wage workers? Evidence from a Swedish payroll tax cut - Sven-Olov Daunfeldt; Anton Gidehag; Hans Seerar Westerberg (Institute of Retail Economics (HFI), 2023)
We use a youth payroll tax cut in Sweden to investigate whether retail firms that were exposed to substantial labor cost savings increased employment of minimum wage workers more than firms that received smaller labor cost savings. Our dataset includes information on both contracted wages and working hours for most employees in the Swedish retail trade industry. The fact that a large portion of retail employees had contracted wages near the negotiated minimum wage levels at the time of the reform suggests that the minimum wage levels were binding to a great extent. We also find that retail firms with large labor cost savings due to the youth payroll tax cut significantly increased both the number of minimum wage hourly employees and their working hours. We observe no such effects for employees with long-term contracts or wages well above the negotiated minimum wages. This suggests that the relatively high minimum wage levels of the Swedish retail industry prevent the employment of workers who are perceived to have low productivity.
Keywords: D24; L25; L26; 330; Retail trade industry; minimum wages; payroll tax reform; natural experiments; collective bargaining